Realizing family food independence through the urban farming concept - Laili Qomariyah; Mariza Ningtyas Febriyanti; Erlanda Nouva Wibowo; Agustin Kana Risqiyani; Miftahul Husnul Suluki; Futun Nur Faridah (Universitas Muhammadiyah Magelang, 2022)
Urban farming is one of the efforts to ensure family food security during the pandemic. Because of their limited mobility and lower income, many people are bored. Residents of RW V are just one example of those who have been affected by the pandemic. This program has the potential to provide independent food security as well as improve the mental health of RW V residents' mothers. Socialization, workshops, training, mentoring, monitoring, and evaluation are some of the methods used. The results of this program show that the residents of RW V are very enthusiastic about urban farming and are capable of growing vegetables. Furthermore, mothers, particularly housewives, report feeling mentally healthier as a result of new activities and a singular focus on urban farming with hydroponics.